Association of Co-Living and Age on the Type of Sports Practiced by Older People - María Antonia Parra-Rizo; Felipe Díaz-Toro; Fatine Hadrya; Patricia Pavón-León; Igor Cigarroa (MDPI AG, 2022)
Introdution: The environment and the type of co-living of older people are crucial to understanding how the nature of their context influences a healthy lifestyle. However, no studies have investigated to what extent their type of co-living may be associated with the sports and the profile practice according to their age. Objective: This study aimed to assess the association between the types of co-living and the age of the physically active elderly and the sports they practice. Hypothesis: It is thought that the age, situation, and satisfaction with the way of living in physically active older people differ according to the type of sport they practice. Methods: Cross-sectional study. We included 358 individuals aged between 61 and 93 years old (M = 69.66, SD = 4.74). Type of co-living was classified as living alone or living with others. The sports activities evaluated were: gym, dance, water activities, and yoga/pilates. Differences in the type of co-living and sports practiced were evaluated by ANOVA or Chi2. Results: Among the elderly who practice gymnastics, most of them live alone and in a tight core (p < 0.001) (Phi = 0.244). Furthermore, those who practice aquatic activities are more frequently the youngest (p < 0.001) (Phi = 0.198). Conclusion: Older people who do gymnastics have smaller living groups, those under 69 opt for gymnastics and aquatic activities, while those aged 70 and over prefer dance, yoga, and pilates.